Does Schooling Cause Growth? - Bils, Mark; Klenow, Peter J (American Economic Review, 2000)
A number of economists find that growth and schooling are highly correlated across countries. A model is examined in which the ability to build on the human capital of one's elders plays an important role in linking growth to schooling. The model is calibrated to quantify the strength of the effect of schooling on growth by using evidence from the labor literature on Mincerian returns to education. The upshot is that the impact of schooling on growth explains less than one-third of the empirical cross-country relationship. The ability of reverse causality to explain this empirical relationship is also investigated. (JEL I2, J24, O4)